CORPORATE COMPLIANCE MANAGEMENT WITH CONSUMER PROTECTION IN ELECTRONIC TRANSACTIONS: CIVIL LAW PERSPECTIVES AND ECONOMIC IMPLICATIONS - Gunawan Widjaja (Adisam Publisher, 2026)
This article analyses corporate compliance management with consumer protection in electronic transactions from two main perspectives: civil law and economic implications. Using a normative legal approach, the analysis focuses on Articles 1320, 1338, and 1365 of the Civil Code, which regulate the validity of agreements, good faith, and tort liability in the digital ecosystem, as well as the application of RegTech to prevent default and the cancellation of unfair standard clauses. From an economic standpoint, compliance has proven to be a value driver with a net national benefit of IDR 5-10 trillion for the 2025-2027 period through a cost-benefit ratio of 3-5x, a reduction in litigation costs of IDR 1.2 trillion/year, and a 40% increase in customer lifetime value, in line with the 2026 digital economy target of USD 130 billion. Recommendations include mandatory ROI compliance reporting by the OJK starting in fiscal year 2027 and Internal Dispute Resolution as the first tier of dispute resolution. This interdisciplinary synthesis provides an actionable blueprint for digital companies, regulators, and legal practitioners for a sustainable electronic transaction ecosystem.